Is there evidence for bacterial transfer via the placenta and any role in the colonization of the infant gut? – a systematic review. (2nd September 2020) - Gil, Angel; Rueda, Ricardo; Ozanne, Susan E.; van der Beek, Eline M.; van Loo-Bouwman, Carolien; Schoemaker, Marieke; Marinello, Vittoria; Venema, Koen; Stanton, Catherine; Schelkle, Bettina; Flourakis, Matthieu; Edwards, Christine A.
Abstract: With the important role of the gut microbiome in health and disease, it is crucial to understand key factors that establish the microbial community, including gut colonization during infancy. It has been suggested that the first bacterial exposure is via a placental microbiome. However, despite many publications, the robustness of the evidence for the placental microbiome and transfer of bacteria from the placenta to the infant gut is unclear and hence the concept disputed. Therefore, we conducted a systematic review of the evidence for the role of the placental, amniotic fluid and cord blood microbiome in healthy mothers in the colonization of the infant gut. Most of the papers which were fully assessed considered placental tissue, but some studied amniotic fluid or cord blood. Great variability in methodology was observed especially regarding sample storage conditions, DNA/RNA extraction, and microbiome characterization. No study clearly considered transfer of the normal placental microbiome to the infant gut. Moreover, some studies in the review and others published subsequently reported little evidence for a placental microbiome in comparison to negative controls. In conclusion, current data are limited and provide no conclusive evidence that there is a normal placental microbiome which has any role in colonization of infant gut.